Loricrin expression and its implication in oral submucous fibrosis, hyperkeratosis and normal mucosa with association to habits - An immunohistochemical study - Nithya S; Elizabeth Joshua; Ranganathan K; Rooban Thavarajah; Umadevi K. Rao (Elsevier, 2019)
Objective: The coarse fibres of areca nut and the continuous friction from occluding teeth are major causes of mechanical stress to the oral mucosa in conditions like oral submucous fibrosis and frictional keratosis. The continuous micro trauma provided in areca nut chewers, creates an environment where the keratinocytes exhibit alteration. Loricrin, is expressed abundantly in keratinizing epithelium in response to mechanical stress. Their expression or absence could play a role in malignant transformation. This study attempts to assess the potential of Loricrin as an early diagnostic marker in patients with chewing habit. Methods: 73 archival samples of formalin fixed, paraffin embedded tissue specimens histopathologically confirmed, were segregated as normal mucosa 11, hyperkeratotic 32 and oral submucous fibrosis 30 and stained with antibodies to Loricrin and graded as negative, mild, moderate and intense based on the staining intensity. Pearson's chi square test was done for statistical analysis. Results: Loricrin expression was observed in all groups with staining in the stratum granulosum showing a significant association to habits (P = 0.000). Conclusion: This prominent staining indicates a compensatory cytoskeletal rearrangement of surface epithelium during cell division in early oral submucous fibrosis showing potential as an early marker of the condition.